Designing a Sustainability Balanced Scorecard at Perumda BPR XYZ - Diana Fitri; Ancella Anitawati Hermawan (Publikasi Indonesia, 2024)
This thesis discusses the proposed design of performance measurement for Perumda BPR XYZ using a sustainability-balanced scorecard approach so that company goals are achieved. With the sustainability balanced scorecard approach, it is hoped that financial and non-financial perspectives as well as sustainability aspects can be measured in balance both in the short and long term. The sustainability balanced scorecard and strategy map explain the relationship between sustainable financial and non-financial perspectives as well as strategic targets and initiatives that can be carried out by companies that are needed to achieve the strategic themes of each perspective. The types of data in this research are primary and secondary, with research instruments used in the form of literature reviews, document analysis and interviews. The research results can be used by Perumda BPR XYZ to design four sustainability balanced scorecard perspectives, which are the sustainability perspective, stakeholder perspective, internal business process perspective and learning and growth perspective which can help companies to achieve the company's short-term and long-term goals.